2021
DOI: 10.1002/adfm.202104899
|View full text |Cite
|
Sign up to set email alerts
|

Large Cumulative Capacity Enabled by Regulating Lithium Plating with Metal–Organic Framework Layers on Porous Carbon Nanotube Scaffolds

Abstract: The high specific capacity of lithium metal is ideal to meet the current demand in rechargeable batteries but lithium dendrites and irreversible volume expansions are major hurdles. 3D lithium host materials can alleviate these problems by lowering the current density with large surface areas and accommodating lithium metal in their pores. However, lithium dendrites are persistently observed because of sluggish lithium‐ion diffusion through tortuous pores, resulting in clogging and thereby dendrite growth. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…By arranging the positions of the lithiophilic/lithiophobic materials, the lithium deposition can be more effectively adjusted. For example, the lithiophilic Au particles can be plated on the bottom of the carbon materials (Xiang et al, 2018;Pu et al, 2019) and the lithiophobic layered metal-organic framework nanosheets can be placed on the top of the 3D framework (Noh et al, 2021) (near the separator) to construct the lithiophiliclithiophobic gradient 3D framework. The gradient 3D framework can guide homogeneous, bottom-up Li deposition and top-down Li dissolution and decrease the formation of lithium dendrite.…”
Section: Discussionmentioning
confidence: 99%
“…By arranging the positions of the lithiophilic/lithiophobic materials, the lithium deposition can be more effectively adjusted. For example, the lithiophilic Au particles can be plated on the bottom of the carbon materials (Xiang et al, 2018;Pu et al, 2019) and the lithiophobic layered metal-organic framework nanosheets can be placed on the top of the 3D framework (Noh et al, 2021) (near the separator) to construct the lithiophiliclithiophobic gradient 3D framework. The gradient 3D framework can guide homogeneous, bottom-up Li deposition and top-down Li dissolution and decrease the formation of lithium dendrite.…”
Section: Discussionmentioning
confidence: 99%
“…[112] Because of the excellent conductivity and other unique features, CNTs have been extensively used to solve the above-mentioned issues and enhance the Coulombic efficiency and electrochemical performances of lithium metal batteries (LMBs). Typically, the strategies for using CNT-based nanomaterials in LMAs include CNT-based Li host design, [23,68,69,71,72,79,83,84,113] modifying current collectors, [41,46,47,[75][76][77]80,82,93] decorating the Li metal surface, [24,42,81] and other strategies. [30,114]…”
Section: The Application Of Cnt-based Nanomaterials In LI Metal Anodementioning
confidence: 99%
“…However, the electric field near the inlet of the pores (i.e., separator side) of the electrode is stronger than the inner part, accelerating the preferential deposition of Li metal and eventually clogging the pore at the inlet (i.e., impairing the inner pores). , To circumvent the clogging problem, the electric field at the pore inlet must be attenuated. Recent studies have shown that thin electronically insulating coating layers such as metal–organic framework and alumina layer are effective, but they require significant efforts to keep the layer thin enough to pass Li + without considerably introducing unwanted impedance. Still, when Li + flux is localized on this type of porous framework, Li dendrites tend to sprout from the surfaces of the porous anodes.…”
Section: Introductionmentioning
confidence: 99%